Core content of the medical school surgical curriculum: Consensus report from the association of surgeons in training (ASIT). (December 2020) - ,; ,; Baker, Daniel; Deekonda, Praveena; Glasbey, James; Humm, Gemma; Mohan, Helen; Nally, Deirdre; Srikandarajah, Nisaharan; Storey, Bradley; Walker, Nathan; Brown, Samuel; et al.
Abstract: Background: The length of time dedicated to the undergraduate surgical curriculum is decreasing. With reduced time on surgical placements, students may be underexposed to their core learning needs. The aim of this study was to reach a national consensus on the core content of the undergraduate surgical curriculum in the UK. This will support medical students and medical schools in designing curricula to meet the core learning needs of students to prepare them for clinical practice. Materials and methods: A proposed consensus document was created, using the Royal College of Surgeons of England undergraduate curriculum as a guide. This was circulated to an external advisory group for electronic suggestions of additional content not already described. Suggestions were discussed with the steering committee prior to inclusion within document. The resulting consensus document was presented to a face-face consensus meeting of medical students and foundation doctors at the Association of Surgeons in Training (ASiT) conference 2019 for live voting. Eighty percent agreement required to reach consensus. Any discussion of topics was transcribed to allow qualitative summary of discussion of those topics which did not reach consensus agreement. Results: Electronic suggestions yielded an extra 8 topics for inclusion into the final consensus document. A total of 52 people participated in the consensus session. The consensus discussed a total of 69 knowledge topics, practical skills and clinical examinations; of which 10 did not reach consensus agreement. Areas failing to reach consensus included knowledge topics in Ear Nose and Throat surgery, Vascular surgery and Neurosurgery as the consensus concluded that these topics were supplementary to core needs. Conclusion: This paper presents a national consensus of the undergraduate surgical curriculum. This document should be used in conjunction with the RCS of England undergraduate curriculum to ensure students have an adequate surgical education.